Respuesta :

Step-by-step explanation:

1/2(6x+1/2)=0

3x+1/4=0

3X=-1/4

X=3(-1/4)

X=-3/4

OR

X=-.75

wyskoj

Answer:

I'll assume you want this simplified.

[tex]\frac{1}{2}*(6x+\frac{1}{2}) = \bold{3x+\frac{1}{4}}[/tex]

Step-by-step explanation:

To simplify, we distribute the outside term [tex]\frac{1}{2}[/tex] to each of the inside terms.

[tex]\frac{1}{2}*(6x+\frac{1}{2}) = (\frac{1}{2} * 6x) + (\frac{1}{2} * \frac{1}{2})[/tex]

[tex]= \frac{6x}{2} + \frac{1}{4} = \bold{3x + \frac{1}{4}}[/tex]